NGO Contracting Evaluation for the HNP Sector in Bangladesh : Evidence and Policy Options - Cortez, Rafael (World Bank, Washington, DC, 2014)
Throughout the world, governments are moving from being exclusively service delivery organizations and toward improving their public health sector management and stewardship capacity. To diversify service provision, the Bangladesh Ministry of Health and Family Welfare (MOHFW) is striving to develop its capability to become active service purchasers in partnership with NGOs and private (for-profit) providers. This report is divided into four chapters. Chapter 1 is an overview of the current role of NGOs in the Bangladesh health sector and maps the NGOs HNP service provision. Chapter 2 reviews the lessons learnt from the national NGO contracting experiences. Chapter 3 describes the performance of selected NGO contracting models and draws lessons learnt using specific criteria related to legal framework and governance aspects, bidding and selection process, flexibility of contracts, supervision and regular monitoring and evaluation, service quality, the accessibility of the poor to services, user satisfaction, and opinions of NGO facility personnel. The findings of the comparative advantage analysis are shown for NGOs, public and private providers at the upazila level in terms of quality, cost, pricing and accessibility. The primary source of information for this task consists of a sample of 50 facilities. This chapter also presents policy options for public and private partnerships, specifically with regards to what to do and how to do it to move forward on strengthening the government's stewardship role and on publicly financing the NGO and private sector to promote diversification of HNP service provision. Finally, Chapter 4 presents the conclusions and recommendations.